Optimization of Ethylene Glycol Plant Heat Exchanger Network with Non-Catalytic Hydration Process from Ethylene Oxide - Muhammad Garin; Elsabella Adiguna; Suprapto Suprapto (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2022)
Heat integration is a method to increase energy efficiency in a series of processes by utilizing the energy potential of other process units, so that Maximum Energy Recovery (MER) will be achieved. One way to perform heat integration is through the design of a heat exchanger network (HEN). The HEN design simulation in this study was carried out in an ethylene glycol plant where in the process there is still a lot of wasted and unused heat. After the HEN simulation was applied, it was found that the heating value decreased by 59% from the existing condition, while the cooling value decreased by 79% from the existing condition. This causes the operation cost for utilities to decrease drastically but increase the capital cost due to the addition of 2 heat exchangers.